Tasawwuf and Its contribution to Islamic da'wah in Terengganu: a Research Study - Mohd Ridzuan Bin Abdullah (Kolej Universiti Islam Malaysia, 2011)
Tasawwuf and its contributions in Islamic propagate research, is a study about Islamic propagate contribution in Terengganu. Tasawwuf is a knowledge, existed since Rasulullah SAW epoch. Although the Islamic religious experts define a different definition about tasawwuf but it only focus to one meaning, contiguously to Allah SWT. Tasawwuf it also one of the method of Rasulullah propagate. Because of that, researcher's focus in this field is to reveal all the propagate contribution. Interview, observation, and historical facts been used as a method in this study. The main objective in this research is to inform the citizen how the tasawwuf assisted to cause a succeed of Islamic propagate. This research had recognized a lot of contributions bought by tasawwuf to expend Islamic propagate especially in Terengganu.